FAM46B is a prokaryotic-like cytoplasmic poly(A) polymerase essential in human embryonic stem cells. Issue 5 (3rd February 2020) - Hu, Jia-Li; Liang, He; Zhang, Hong; Yang, Ming-Zhu; Sun, Wei; Zhang, Peng; Luo, Li; Feng, Jian-Xiong; Bai, Huajun; Liu, Fang; Zhang, Tianpeng; Yang, Jin-Yu; et al.
Abstract: Family with sequence similarity (FAM46) proteins are newly identified metazoan-specific poly(A) polymerases (PAPs). Although predicted as Gld-2-like eukaryotic non-canonical PAPs, the detailed architecture of FAM46 proteins is still unclear. Exact biological functions for most of FAM46 proteins also remain largely unknown. Here, we report the first crystal structure of a FAM46 protein, FAM46B. FAM46B is composed of a prominently larger N-terminal catalytic domain as compared to known eukaryotic PAPs, and a C-terminal helical domain. FAM46B resembles prokaryotic PAP/CCA-adding enzymes in overall folding as well as certain inter-domain connections, which distinguishes FAM46B from other eukaryotic non-canonical PAPs. Biochemical analysis reveals that FAM46B is an active PAP, and prefers adenosine-rich substrate RNAs. FAM46B is uniquely and highly expressed in human pre-implantation embryos and pluripotent stem cells, but sharply down-regulated following differentiation. FAM46B is localized to both cell nucleus and cytosol, and is indispensable for the viability of human embryonic stem cells. Knock-out of FAM46B is lethal. Knock-down of FAM46B induces apoptosis and restricts protein synthesis. The identification of the bacterial-like FAM46B, as a pluripotent stem cell-specific PAP involved in the maintenance of translational efficiency, provides important clues for further functional studies of this PAP in the early embryonic development of high eukaryotes.